Fast and continuous on‐load voltage regulator based on electronic power transformer. Issue 6 (1st July 2013) - Yang, Jiawei; Mao, Chengxiong; Wang, Dan; Lu, Jiming; Fu, Xueqiang; Chen, Xun
Abstract : The on‐load tap changing transformers have been widely used for their ability to maintain output voltages at desired levels despite the load or voltage changes in the ac mains. However, they present several disadvantages such as slow response, high‐maintenance cost and discontinuous voltage regulation. This study proposes a novel on‐load voltage regulator based on electronic power transformer (OLVR‐EPT) to eliminate these drawbacks. By injecting an appropriate voltage component to traditional power transformer windings through EPT output stage, the resultant load voltage can be maintained at the desired value. There are no tap‐changers anymore, so the voltage regulation is fast and continuous. Two sample schemes of OLVR‐EPT are given and corresponding control method is developed in this study. The simulation and experimental results demonstrate that OLVR‐EPT is able to maintain load voltages at the desired value effectively.